2014
DOI: 10.21608/jappmu.2014.70665
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effects of Feeding Fish the Dried-Treated Sewage Sludge: I-Concerning Growth Performance, Feed Utilization and Chemical Composition

Abstract: A field study was conducted to investigate the effects of feeding fish [in a polyculture system consists of four freshwater species, namely Nile tilapia (T), silver carp (Sc), common carp (Cc), and African catfish (Cf)] the sewage (S) sludge comparing with a commercial diet for fish as a control (C) for 102days. From the obtained results, the use of sewage sludge in fish feeding led to lower growth performance. Silver carp reflected better growth performance than Nile tilapia, common carp and catfish, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…The negative effect of feeding DSS on the mortality rate may be due to its very high content of ash and very low percentages of EE and total carbohydrate comparing to the commercial (control) diet (Table 1), as well as due to the long period of exposure time (102 days). That affected also negatively the growth performance and feed utilization (Abdelhamid et al, 2014, complementary study to the present study). Also, the present study suggests a strong link between metals bioaccumulation in rearing water, fish body and muscles from one side and the morphological lesions and the survival rateof the experimental fish from the other side.…”
Section: Morphological Lesionssupporting
confidence: 70%
“…The negative effect of feeding DSS on the mortality rate may be due to its very high content of ash and very low percentages of EE and total carbohydrate comparing to the commercial (control) diet (Table 1), as well as due to the long period of exposure time (102 days). That affected also negatively the growth performance and feed utilization (Abdelhamid et al, 2014, complementary study to the present study). Also, the present study suggests a strong link between metals bioaccumulation in rearing water, fish body and muscles from one side and the morphological lesions and the survival rateof the experimental fish from the other side.…”
Section: Morphological Lesionssupporting
confidence: 70%
“…The maximum feed conversion ratio was between days 10 and 20. Nile tilapia fed with the sewage sludge showed the best feed conversion ratio (3.18) compared to silver carp and common carp (Abdelhamid et al 2014). Liney et al (2006) reported that after 3 months of rearing in 80 % secondary treated waste water.…”
Section: Resultsmentioning
confidence: 99%
“…Although many people in Kafr El-Sheikh Governorate (as the highest governorate allover Egypt in producing fish) talk about sewage using in fish nutrition; yet, different freshwater fish species (Nile tilapia, silver carp, common carp, and African catfish) reflected low values of all tested measurements (growth, feed utilization, and fish body composition, dressing, and boneless meat) by their feeding with sewage comparing with those fed commercial-artificial diet. Thus, Abdelhamid et al (2014) recommended do not feeding fish with treated sewage. Final total length and condition factor of the experimental fish The calculated condition factor (CF) of the experimental fish at the start of the experiment was 2.018%, since the initial body weight and total length were 17.3 g and 9.5 cm, respectively.…”
Section: Final Live Body Weight Of the Experimental Fishmentioning
confidence: 99%